The experience of electroconvulsive therapy and its impact on associated stigma: A meta-analysis. (December 2016) - Aoki, Yuta; Yamaguchi, Sosei; Ando, Shuntaro; Sasaki, Natsuki; Bernick, Peter J; Akiyama, Tsuyoshi
Background: Despite its efficacy and safety, electroconvulsive therapy (ECT) is underutilized, in part due to stigma associated with the treatment. Aims: The aim of this study was to test the hypothesis that experiencing ECT has an impact on associated stigma, as measured by patient and family knowledge of and attitudes toward ECT. Methods: A comprehensive literature search was conducted using MEDLINE, EMBASE and PsycINFO. Studies with cross-sectional and/or longitudinal designs were identified. Studies were further categorized into subcategories based on participant type (patients or patient family members) and outcome domain (knowledge or attitudes). Effect size (Cohen's d ) was calculated for each study and then integrated into each subcategory (participant type by outcome domain) using a random effect model. Results: Eight studies were identified as being eligible for analysis. Two studies were cross-sectional, five were longitudinal and one incorporated both designs. Analysis of the longitudinal studies indicated that experiencing ECT both increased knowledge of and improved attitudes toward ECT in patients; in family members of patients, analysis showed significant positive change in knowledge of ECT, but no significant change in attitudes toward ECT. Conclusion: Experience with ECT may have a positive impact on knowledge of and attitudes toward ECT. However, the quality of evidence of included studies was low; further research is required in order to clarify the relationship and to identify information of use to individuals considering ECT as a treatment option.